Inactivation efficacy and reactivation of fecal bacteria with a flow-through LED ultraviolet reactor: Intraspecific response prevails over interspecific differences. (April 2023) - Romero-Martínez, Leonardo; Duque-Sarango, Paola; González-Martín, Claudia; Moreno-Andrés, Javier; Acevedo-Merino, Asunción; Nebot, Enrique
Abstract: Treatment with ultraviolet (UV) light is a common option for inactivating waterborne organisms. The mercury vapor lamps conventionally used as a source of UV-C light for water disinfection are eventually replaced by light emitter diodes (LEDs) in the middle term due to their higher efficiency and lack of hazardous materials. Nonetheless, biological mechanisms for repairing UV damage caused by the UV treatment are some of its significant undesirable features. The objective of this study is to evaluate and compare the UV-resistance and the reactivation degree in different strains of E. coli and E. faecalis treated with a flow-through reactor equipped with LEDs with an emission range between 265 and 285 nm. The treated organisms were subjected to various illumination regimes after the UV irradiation. The results obtained indicated that intraspecific differences between the strains of E. coli were greater than the interspecific differences with respect to E. faecalis in terms of UV-resistance and repairing potential. The UV doses necessary to achieve four log-reductions ranged from 10.2 to 16.3 mJ cm −2 for E. coli and from 11.1 to 11.4 for mJ cm −2 for E. faecalis . Dark repair was not observed within 24 h after the UV irradiation whereas the degree of photorepair depended on both the bacteria strain and the applied UV dose. The exposure of the irradiated organisms to an illuminated environment entailed and increasing between the 18 % and the 160 % of the UV dose required to achieve four log-reductions. Graphical abstract: Unlabelled Image Highlights: The UV resistance of different strains of E. coli and E. faecalis has been compared. The intraspecific differences were greater than the interspecific differences. The UV-resistance of E. faecalis was similar to E. coli using UV-LEDs. Dark repair was negligible, but photorepair was significant. The photoreactivation increased the UV doses necessary for the treatment.